Metodología para empoderar y comprometer a la alta dirección de las PYMES en la implementación y mantenimiento del sistema de gestión de la calidad (2020)
The SMEs are part of a large percentage of companies in Colombia, specifically the 99.6% of the country, these ones generate a third of the annual gross domestic product and achieve giving 67% of jobs to Colombians. This being not a minor data, there is a significant increase in SMEs that are choosing to grow rapidly and consider that one of the best ways to achieve this is by acquiring a quality certification. It was identified that one of the biggest drawbacks today are the lack of empowerment and commitment of SME managers in the implementation and maintenance of the quality management system. Therefore this work has as purpose of structuring a methodology that manages to empower and commit senior management of SMEs, based on Jürgen Klarić's commercial methodology, which consists of knowing biologically and culturally the client, in this case the client would be the SMEs leader. The present study showed that one of the main drawbacks of the management of SMEs in the implementation of this system is the ignorance of the benefits generated by the quality management system and the functions that must be fulfilled for this to happen, In this way, it is considered that the methodology with the six identified sales elements can generate a positive change in the commitment and empowerment of the managers of the SMEs.